RETRACTION: Speech Culture Improvement in the Process of Working with Prepositional Constructions with no - Halyna Tkachuk; Halyna Dorosh (Pedagogical Discourse, 2011)
Retraction date: 02.04.2019.The article was retract because apparently represents plagiarized material from results scientific researchs G.Semerenko (Семеренко Г. Удосконалення культури мовлення у роботі над конструкціями з прийменником по. Шляхи піднесення культури мовлення: теорія і практика / за заг. ред. Г. Семеренко. Київ: НПУ імені М.П.Драгоманова, 2008. С. 349–373.).The article deals with the problem of speech culture improvement on the morphological level, particularly with using prepositional constructions with no in the process of translating from Russian.